KEBERADAAN KAPANG-KAPANG PENGKONTAMINASI ASAM KANDIS (Garcinia xanthochymus Hook.f.) YANG DIJUAL DI PASAR RAYA KOTA PADANG - Aspirin, Anik; Fifendy, Mades; Nurmiati, Nurmiati (STKIP PGRI Sumbar, 2013)
ABSTRACT Kandis Acid plant (Garcinia xanthochymus Hook.f.) is one herb that is intertwined with everyday dishes. Almost all dishes Padang wearing kandis acids, especially fish based dishes. Damage foodstuffs by microorganisms has been happening since the material is located in the field (orchard) until the material is transported, stored and traded. Sources of microorganisms destroyer kandis acid can come from the environment, equipment or hand manager (human) itself. Mold are microorganisms that are found in food, including kandis acid. Mycotoxins are toxins released by mold and are detrimental to health. This study aims to determine the types of mold contaminants on kandis acid (Garcinia xanthochymus Hook.f.) sold in Pasar Raya Padang.The research was conducted in July and August 2013 at the Labolaturium Microbiology University of Andalas, by using the method survay descriptive survey is to undergo directly to Kandis acid in Pasar Raya Padang, further research, the results in the identification using reference books Barnett and Samson and Hoekstra subsequently described. Based on the results, the six species of three genus mold Kandis acid contaminating namely: Aspergillus niger, Aspergillus sp.1 suspected Aspergillus oryzae, Aspergillus sp.2 suspected Aspergillus flavus, Penicilim sp.1, Penicillium sp.2, Rhizopus oryzae, So Kandis acid is sold in Pasar Raya Padang contaminated by mold.